1985
DOI: 10.1067/mva.1985.avs0020727
|View full text |Cite
|
Sign up to set email alerts
|

Endothelium develops on seeded human arterial prosthesis: A brief clinical note

Abstract: Despite a considerable and growing body of evidence that endothelial cell seeding accelerates the healing of arterial prostheses in laboratory animals, there has been no histologic evidence thus far to indicate that a similar process occurs in human beings. A case is reported of histologically confirmed, extensive endothelial healing on a polytetrafluoroethylene femoropopliteal bypass graft 90 days after it was seeded and implanted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

1989
1989
2009
2009

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…2). 2 In a pilot study, seeded PTFE grafts resulted in significantly better patency than unseeded grafts. 8 The experience with endothelial seeding was subsequently extended to include 41 patients with femoral-popliteal bypass grafts thus far.…”
Section: Femoral-popliteal Results With Polytetrafluoroethylenementioning
confidence: 98%
See 1 more Smart Citation
“…2). 2 In a pilot study, seeded PTFE grafts resulted in significantly better patency than unseeded grafts. 8 The experience with endothelial seeding was subsequently extended to include 41 patients with femoral-popliteal bypass grafts thus far.…”
Section: Femoral-popliteal Results With Polytetrafluoroethylenementioning
confidence: 98%
“…1 Our strategy for reducing the formation of thrombus and the stimulated replication of fibroblasts is to restore the endothelial lining more rapidly. Endothelial seeding is a method that transplants autogenous endothelium to the site of damage, hastens the development of a completely endothelialized surface, 2,3 improves platelet survival, 4 reduces platelet serotonin release, 4 and improves the resistance of prosthetic grafts to clotting during periods of reduced flow. 5…”
mentioning
confidence: 99%
“…Herring and coworkers (67) showed that EC seeding in humans results in endothelialization. The results of the initial clinical trials of single‐stage seeding using vein as a source of ECs were variable but mainly disappointing (24,55,68–74).…”
Section: Methodsmentioning
confidence: 99%
“…Another approach searched to combine the advantages of the synthetic grafts with the biological characteristics of an active endothelial intima (43,44). Many investigators have then tried to seed endothelial cells (44)(45)(46)(47)(48)(49)(50)(51), mesothelial cells (52,53) or bone marrow cells (54,55) upon the synthetic grafts. These attempts have been hampered by the weak attachment of endothelial cells to these various surfaces.…”
Section: Small Diameter Tissue-engineered Blood Vesselsmentioning
confidence: 99%